2022
DOI: 10.1590/1980-220x-reeusp-2021-0488en
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Stress and Digital Literacy on Student Satisfaction with Distance Education

Abstract: Objective: To examine the relationship between perceived stress/digital literacy and student satisfaction in health science college students in the distance education process. Method: The cross-sectional study was conducted by collecting data from 842 students. The dependent variable was student satisfaction in distance education. For the analyses, t-test, ANOVA (post hoc: Bonferroni), and linear regression methods were used. Results: Distance education student satisfaction was 178.21 ± 48.64. Student satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
2
1
1
Order By: Relevance
“…Further thematic analysis of the study data also indicated that there was no link between perceived competency with technology and overall satisfaction with OL and assessment. This is inconsistent with research by Vermisli et al [23] which found that student satisfaction was high amongst students who had increased digital literacy though it is important to note this can be di cult to measure and various tools have been proposed. The lack of link between perceived competency with technology and overall satisfaction slightly contradicts the fact that in terms of facilitating an improved student experience of OL there was a theme relating to technology understanding, improved wiand improved information technology (IT) skills.…”
Section: Discussioncontrasting
confidence: 67%
“…Further thematic analysis of the study data also indicated that there was no link between perceived competency with technology and overall satisfaction with OL and assessment. This is inconsistent with research by Vermisli et al [23] which found that student satisfaction was high amongst students who had increased digital literacy though it is important to note this can be di cult to measure and various tools have been proposed. The lack of link between perceived competency with technology and overall satisfaction slightly contradicts the fact that in terms of facilitating an improved student experience of OL there was a theme relating to technology understanding, improved wiand improved information technology (IT) skills.…”
Section: Discussioncontrasting
confidence: 67%
“…27,31 An adequate technical infrastructure, reliable internet access, and skills in information and communication technology (ICT) are essential for E-learning programs to work. 10,28,32,33 In our study, the technical aspects and functionality of the platforms were rated as being good. This may not be applicable to all countries, since ICT access and competence are high in Finland.…”
Section: What This Study Addsmentioning
confidence: 71%
“…In today's constantly evolving technological ecosystem, developing and applying digital literacy skills enables learners to build and use emotional intelligence, allowing them to negotiate problems with a better awareness of their own and others' emotions [19]. Moreover, digital literacy has a signi cant impact on academic stress levels, as students experience a decline in stress when they have con dence in their digital skills and abilities [20] [21] [22]. It is crucial to combine emotional intelligence and digital competence in the realm of technology [23] [17].…”
Section: Introductionmentioning
confidence: 99%